The Influence of Slang on the Decline of Language Literacy in the Young Generation of Indonesia: Language Literacy - Novhira Putri Paino; M. Joharis Lubis; Surya Masniari Hutagalung (Yayasan Adra Karima Hubbi, 2024)
Background. The increasing use of slang among Indonesian youth has raised concerns about its impact on language literacy and formal communication skills. Purpose. To examine the influence of slang on language literacy decline among Indonesian youth and its implications for formal language skills, social identity, and intergenerational relations. Method. A mixed-method study was conducted in Jakarta, Surabaya, and Medan, employing in-depth interviews, surveys, and social media content analysis. Data were collected from 150 respondents to assess slang usage patterns and their impact on formal language capabilities. Results. The study revealed that 80% of frequent slang users struggled with formal language in academic settings, while 65% reported diminished essay-writing abilities. Additionally, 70% identified slang as integral to their social identity, though 60% experienced communication difficulties with older generations. Social media platforms significantly influenced slang adoption, with 90% of respondents regularly using slang on Instagram and TikTok. Conclusion. The findings demonstrate a significant correlation between frequent slang usage and declining formal language literacy among Indonesian youth. This trend affects academic performance and intergenerational communication, highlighting the need for balanced language education strategies that preserve formal literacy while acknowledging youth linguistic identity.